1995
DOI: 10.1002/j.1460-2075.1995.tb00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Myc-dependent step during the formation of active G1 cyclin-cdk complexes.

Abstract: Activation of conditional alleles of Myc can induce proliferation in quiescent cells. We now report that induction of Myc in density‐arrested fibroblasts triggers rapid hyperphosphorylation of the retinoblastoma protein and activation of both cyclin D1‐ and cyclin E‐associated kinase activities in the absence of significant changes in the amounts of cyclin‐cdk complexes. Kinase activation by Myc is blocked by inhibitors of transcription and requires intact DNA binding and heterodimerization domains of Myc. Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
215
2

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(237 citation statements)
references
References 80 publications
20
215
2
Order By: Relevance
“…One possibility is that overexpression of D-or E-type cyclins leads to a higher associated kinase activity simply because more cyclin/CDK complexes are formed. However, higher cyclin/CDK kinase activity is not necessarily linked to higher amounts of the individual partner proteins because it depends on the activity of CAKs (CDK activating kinases) and the degree of phosphorylation (for a review see Draetta, 1997) and, in addition, cyclin/ CDK kinase complexes can be activated by releasing them from inactive high molecular weight complexes with inhibitors by still poorly de®ned biochemical steps (Steiner et al, 1995;Vlach et al, 1996). Thus, higher levels of a particular cyclin would not necessarily lead to the formation of more cyclin/CDK dimers with kinase activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One possibility is that overexpression of D-or E-type cyclins leads to a higher associated kinase activity simply because more cyclin/CDK complexes are formed. However, higher cyclin/CDK kinase activity is not necessarily linked to higher amounts of the individual partner proteins because it depends on the activity of CAKs (CDK activating kinases) and the degree of phosphorylation (for a review see Draetta, 1997) and, in addition, cyclin/ CDK kinase complexes can be activated by releasing them from inactive high molecular weight complexes with inhibitors by still poorly de®ned biochemical steps (Steiner et al, 1995;Vlach et al, 1996). Thus, higher levels of a particular cyclin would not necessarily lead to the formation of more cyclin/CDK dimers with kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously proposed that one signalling pathway of cyclin D/CDK4 functions via the phosphorylation of the Rb related pocket protein p107 and the release of the Myc/Max transcription factor (Beijersbergen et al, 1994(Beijersbergen et al, , 1995Gu et al, 1994). Taking into account recent ®ndings about the activation of the cyclin E/ CDK2 kinase by the induction of Myc through conditional alleles (Steiner et al, 1995) we had postulated that Myc acts downstream of cyclin D/ CDK4 and is regulated via the Rb related pocket protein p107 that is in turn uncontrolled by cyclin D/CDK4 activity and p16 (Haas et al, 1997). In this model, Myc was placed upstream of cyclin E/CDK2 (Steiner et al, 1995) and downstream of cyclin D/CDK4 (Haas et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the expression of p27 cyclin-dependent kinase (cdk) inhibitor is under negative posttranslational regulation by c-Myc (Steiner et al, 1995). Since p27 has been shown to confer resistance against anticancer agents to tumor cells (Croix et al, 1996), it appeared likely that p27 has antiapoptotic activity similar to other cdk inhibitors such as p16 and p21 (Wang and Walsh, 1996;Poluha et al, 1996).…”
Section: Pim-1 Stimulates Rather Than Inhibits C-myc-mediated Apoptosismentioning
confidence: 99%